A comparison of nanoparticle-antibody conjugation strategies in sandwich immunoassays. Issue 4 (4th July 2017) - Tam, Justina O.; de Puig, Helena; Yen, Chun-wan; Bosch, Irene; Gómez-Márquez, Jose; Clavet, Charles; Hamad-Schifferli, Kimberly; Gehrke, Lee
ABSTRACT: Point-of-care (POC) diagnostics such as lateral flow and dipstick immunoassays use gold nanoparticle (NP)-antibody conjugates for visual readout. We investigated the effects of NP conjugation, surface chemistries, and antibody immobilization methods on dipstick performance. We compared orientational, covalent conjugation, electrostatic adsorption, and a commercial conjugation kit for dipstick assays to detect dengue virus NS1 protein. Assay performance depended significantly on their conjugate properties. We also tested arrangements of multiple test lines within strips. Results show that orientational, covalent conjugation with PEG shield could improve NS1 detection. These approaches can be used to optimize immunochromatographic detection for a range of biomarkers.